The Application of Emotional Experience in Chinese Reading Teaching - Li, Li (Journal of Education and Educational Technologies, 2023)
Positive psychology is a science that studies positive qualities such as human character and development potential, emphasizing the study of positive factors in psychological life. It includes three aspects: positive personality, positive emotional experience, and positive social system. People are increasingly paying attention to the mental health issues of college students, and introducing the concept of positive psychology into the mental health education system of college students can improve the quality of their education.